REKONSTRUKSI STRUKTUR GEOLOGI DI BINUNGAN BLOK 1-2 DAN PARAPATAN, KECAMATAN TANJUNGREDEB, KABUPATEN BERAU, KALIMANTAN TIMUR - Alfeus Yunivan Kartika (Geological Engineering E-Journal, 2013)
The research area is administratively located in Binungan Block 1-2 and Parapatan Block, TanjungredebDistrict, Berau, East Kalimantan. Binungan 1 – 2 and Parapatan which owned by PT. Berau Coal, separated by KelaiRiver. The purpose of this study was to determine the geological structure in both block based on the correlation of thewell drilling and surface data. The research used field observations to obtain data on surface geology also wellcorrelation using e-logging data, consist of gamma ray log, caliper log, short density log, and long density log. Surfacedata analysis using stereonet to get the main stress affecting in research area and evolving types of geological structures.Well correlation is a basic method in geological structure reconstruction, which conducted to determine subsurfacecondition. Lithology of research area, from old to young consisted of clayey sandstone and sandstone units, whichincluded in Middle Miocene aged, Latih Formation and Holocene aged alluvium sediments. The result of data analysisindicated that the geological structures type that evolved in the research area is a plunging syncline with the axistrending north – south and sinistral – wrench fault trending west – east. Syncline is folded sorrounding rocks on the bothblocks and continuous from Binungan 1-2 to Parapatan. The sinistral – wrench fault in Kelai River caused the shiftingposition of the axis of syncline. The geological structure formed during the Pliocene as a result of the coupling faultsliding motion in north and south area of research location. Mechanism of geological structure formation in researcharea begins with syncline formation with axis trending north – south, the force continues causes the formation of thethird order strike – slip fault from mangkalihat fault. This strike – slip fault causes the folds axis cutted and shifted, alsocaused the plunging syncline.